2009
DOI: 10.1073/pnas.0905550106
|View full text |Cite
|
Sign up to set email alerts
|

Microwell-mediated control of embryoid body size regulates embryonic stem cell fate via differential expression of WNT5a and WNT11

Abstract: Recently, various approaches for controlling the embryonic stem (ES) cell microenvironment have been developed for regulating cellular fate decisions. It has been reported that the lineage specific differentiation could be affected by the size of ES cell colonies and embryoid bodies (EBs). However, much of the underlying biology has not been well elucidated. In this study, we used microengineered hydrogel microwells to direct ES cell differentiation and determined the role of WNT signaling pathway in directing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
359
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 357 publications
(377 citation statements)
references
References 40 publications
(57 reference statements)
7
359
0
2
Order By: Relevance
“…6,[11][12][13] Interestingly, both cell fate and cell function can be influenced by the hydrogel microenvironment. [14][15][16] Thus, ideally the hydrogel microenvironment should mimic the mechanical and biological demands and requirements of the tissues being replicated. 17 In the present study we have developed a photocrosslinkable composite hydrogel made from poly(ethylene glycol) dimethacrylate (PEGDMA MW 1000 Da) and methacrylated gelatin (GelMA).…”
Section: Introductionmentioning
confidence: 99%
“…6,[11][12][13] Interestingly, both cell fate and cell function can be influenced by the hydrogel microenvironment. [14][15][16] Thus, ideally the hydrogel microenvironment should mimic the mechanical and biological demands and requirements of the tissues being replicated. 17 In the present study we have developed a photocrosslinkable composite hydrogel made from poly(ethylene glycol) dimethacrylate (PEGDMA MW 1000 Da) and methacrylated gelatin (GelMA).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of photolithographically patterned poly(ethylene glycol) diacrylate (PEGDA) enables to fabricate microwell array [26,27], cultures cells inside hydrogels [28], and forms cell-laden 2 Advances in OptoElectronics microgels for the fabrication of 3D tissue constructs [29]. The high-resolution feature of photolithographically patterned PEGDA hydrogel has been also applied to photoresistbased patterns [30] as master molds for generating poly(dimethylsiloxane), PDMS, microstructures [31].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important factors is the size and morphology of EBs. 1,4-7 For example, Hwang et al 8 demonstrated that cardiogenesis was enhanced in larger EBs, while endothelial cell differentiation was increased in smaller EBs. Furthermore, Choi et al 9 performed stem cell differentiation from the EBs with controlled dimensions, and they found that the cardiogenesis and neurogenesis were strongly regulated by the EB dimensions.…”
Section: Introductionmentioning
confidence: 99%